Cartography of Resistance: Amplifying Female Voices and Narratives - Silva , Geisa Katiane da; Sanmartin , Stela Maris (Farol, 2024)
The exhibition “Fratura”, which was on display from September to November 2024 at Galeria Homero Massena, by artist Geisa da Silva, brings out the complexities of women's stories over time and how these stories, when revealed, raise significant questions about the visibility of forgotten and silenced narratives. Exploring how women's stories can be reconstructed through cartography, connecting points of intersection across different historical periods and geographies, offers an opportunity to understand the complexities of their experiences and identities.
Keywords: Visual arts; Art Teaching